A study of low power laser on the regenerative process of Girardia tigrina (Girard,1850) (Turbellaria; Tricladida; Dugesiidae) - Lopes,KAR. (2009)
The mechanism of regeneration does not start to restore the wound until its corresponding epimorphic phase. A bioestimulation of tissues and cells by laser radiation depends on the wavelength, on the dose, and on the intensity of the light. The goal of this work was to verify the effect of the low power laser at 660 nm on the regenerative process of Girardia tigrina. The specimens were maintained in the laboratory under a temperature ranging from 19° up to 24 °C for 21 days. The planarians were anesthetized by placing them on ice and then cut them with a scalpel. The three treatments were as following: animals individually irradiated with 14 sessions with 1 minute duration (treatment 1), 14 sessions with 3 minutes duration (treatment 2), and without irradiation (control). The planarians were amputated and divided in three study treatments: a control group (without radiation), and two other treatments: irradiated for 1 minute, and irradiated for 3 minutes. The animals were irradiated with diode laser (660 nm) with 3.3 ± 0.3 mW of power, using 0.94 mW.mm-2 power density for each irradiation procedure. During the experiment, 14 irradiation sessions were undertaken. The specimens were fixed in Bouin, and stained with hematoxyline and eosin. From observation and histological analysis, it was possible to assess the effects of interaction between laser and tissue. The head fragment after 1 minute of irradiation presented a better organized tissue scheme, when compared with the other treatments. Aspects of the body fragments submitted to 3 minutes of light treatment were very similar to fragments that had not been injured. It can be concluded that there are changes in the quality of regeneration when treated with low power laser under the conditions mentioned above.